1997
DOI: 10.1124/mol.52.6.958
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Human GlutathioneS-Transferase μ Cluster Containing a DuplicatedGSTM1Gene that Causes Ultrarapid Enzyme Activity

Abstract: The mu class glutathione S-transferase gene GSTM1 is polymorphic in humans, with approximately half of the Caucasian population being homozygous deleted for this gene. GSTM1 enzyme deficiency has been suggested to predispose people to lung and bladder cancer. Some people in a Saudi Arabian population, however, have been described previously with ultrarapid GSTM1 enzyme activity. Here we have evaluated the molecular genetic basis for this observation. Genomic DNA from two Saudi Arabian subjects exhibiting ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 38 publications
1
59
0
Order By: Relevance
“…This SNP results in two new alleles -GSTM1*A and GSTM1*B, which were reported to be functionally identical (McLellan et al, 1997). In addition, a duplication of GSTM1 gene has been identified and characterized (GSTM1*1x2 allele) in people who displayed ultrarapid GSTM1 activity (McLellan et al, 1997). Thus, four allele loci have been described in the human GSТМ1 -GSТМ1*А, GSТМ1*B, GSТМ1*0 and GSTM1*1x2, which determine several phenotypes.…”
Section: Gstm Classmentioning
confidence: 99%
See 2 more Smart Citations
“…This SNP results in two new alleles -GSTM1*A and GSTM1*B, which were reported to be functionally identical (McLellan et al, 1997). In addition, a duplication of GSTM1 gene has been identified and characterized (GSTM1*1x2 allele) in people who displayed ultrarapid GSTM1 activity (McLellan et al, 1997). Thus, four allele loci have been described in the human GSТМ1 -GSТМ1*А, GSТМ1*B, GSТМ1*0 and GSTM1*1x2, which determine several phenotypes.…”
Section: Gstm Classmentioning
confidence: 99%
“…The close proximity of GSTM1 and GSTM2, as well as the presence of two almost identical 4.2-kb regions flanking the GSTM1 gene have been suggested to be the reasons for the observed entire GSTM1 gene deletion resulting in a null GSTM1 allele (GSTM1*0) (Pearson et al, 1993;Bolt &Thier, 2006). Furthermore, a transversion of G with C at position 534 (534G>C, formerly noted as 519G>C ) was described leading to a substitution of 172Lys with 172Asn (formerly Lys 173 Asn) (McLellan et al, 1997;Bolt &Thier, 2006;McIlwain et al, 2006;Gao et al, 2010). This SNP results in two new alleles -GSTM1*A and GSTM1*B, which were reported to be functionally identical (McLellan et al, 1997).…”
Section: Gstm Classmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The five human GSTM genes are organized in a gene cluster on chromosome 1p13.3 12,13 and are well known to be highly polymorphic. [15][16][17] About 50% of the human population carries polymorphic deletions for GSTM1 gene (Xu et al 18 and the references therein). The variants of the genes have been tightly linked to susceptibility to carcinogens and toxins, as well as to toxicity and efficacy of certain drugs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that GSTM1 catalyzes a glutathione conjugate of catecholamine o-quinones such as aminochrome (Smythies et al, 1998). GSTM1 has an entire gene deletion polymorphism and its enzymatic activity is classified into three grades, i.e., a highly active genotype (homozygous non-deletion alleles; NN), a moderately active genotype (heterozygous non-deletion alleles; DN), and a null genotype (homozygous deletion alleles; DD) (McLellan et al, 1997). Recently, it has been reported that the frequency of D allele of GSTM1 gene in the patients with schizophrenia was significantly (p=0.0075) higher than that of normal controls, suggesting that GSTM1 gene may be associated with an increased susceptibility to schizophrenia (Harada et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%